A comparative assessment of emotional intelligences and happiness index among normal sighted and visually impaired students - Raimule, Madhur; Bhawalkar, J. S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Emotional development is also strongly affected by infantile and childhood visual impairment. Visually impaired infants may not respond and smile to human faces and may be misjudged as indifferent to social contact. Emotional development is also strongly affected by infantile and childhood visual impairment. Happiness, or “subjective wellbeing”, a term that is used synonymously, refers to the subjective assessment of quality of life. Methods:A descriptive cross sectional study was conducted in a residential school for visually impaired and another residential school for normal sighted students in 1:2 proportions. Emotional intelligence of participants was calculated using Trait Emotional Intelligence Questionnaire Children Short form. The Oxford Happiness Questionnaire (OHQ) has been derived from the Oxford Happiness Inventory. OHQ comprises 29 items. The data was analysed using statistical tool available in SPSS version 20. Results: Mean ages of visually impaired student were 12.37 where as in normal students it was 11.71. Mean emotional intelligence score for normal sighted students was 135.98with SD=8.49. In case of visually impaired students it was 107.93 with SD=10.25. Mean happiness index among normal sighted students was3.98 with SD=0.675. Among visually impaired students it was 3.03 with SD=0.471. There was moderate, positive correlation between social quotient and emotional intelligence which is statistically significant. Conclusions:Mean Trait-EI score was significantly lower among visually impaired student compared with normal sighted students. Happiness quotient was calculated using Oxford happiness questionnaire. Mean happiness quotient was significantly lower among visually impaired students as compared with normal sighted controls. Emotional intelligence was found to be positively correlated with the happiness quotient.